Associação entre fatores fisiopatológicos, capacidade e desempenho funcionais na doença de Chagas - Lidiane Aparecida Pereira de Sousa (2008)
Chagas disease (CD) is still a major health problem in endemic areas. Chagas cardiomiopathy comprises tromboembolism, arrhythmia and ventricular dysfunction. Moreover, CD patients frequently present dyspnea, effort intolerance and consequently daily-life activity limitations. Therefore, the purpose of this study was to verify, by means of two different studies, association between physiopathology factors and functional variables in CD patients. In the first study, we analyzed theassociation between levels of natriuretic peptide type B (BNP), monocytechemoattractant protein -1 (MCP-1), left ventricle ejection fraction (FEVE) and distance walked during the six-minute walk test (6MWT). The results showed a significant and negative correlation between the distance reached in the 6MWT and increased circulating levels of MCP-1 (r=- 0.358, p= 0.04) and BNP (r=-0.349, p=0.04), as well as a direct correlation with FEVE deterioration (r= 0.451, p=0.004), indicating that the 6MWT could constitute an auxiliary tool when evaluating CD patients. On the other hand, in the second paper, it was studied the association between vagal heart rate variability (HRV) indexes and the level of physical activity,evaluated by the International Physical Activity Questionnaire (IPAQ), for Chagas disease patients and control subjects. In the control group, it was observed a significant association between habitual physical activity and vagal HRV indexes, but in the CD group, no correlation was found, suggesting that Chagas dysautonomia disrupted this associatio